The differences of glycodelin and uterus NK cell expression in obese and non-obese rats (Rattus norvegicus) - Diyah Nofita Ofa Ningtriyas; Arsana Wiyasa; Muhammad Nooryanto (Universitas Airlangga, 2021)
HIGHLIGHTS 1. Obesity increases the risk of comorbidities especially for the pregnancy. 2. The study analyzed glycodelin levels and uterine NK cell expression using Rattus norvegicus as animal model. 3. uNK cell expression of the obese rats group was higher as the marker of chronic inflammation for obesity. 4. Although there was increasing uNK cells in obese rats group, this result was not followed by the level of gycodelin. ABSTRACT Objectives: To prove the existence of differences in glycodelin levels and uterine NK cell expression in obese and non-obese female white rats of Wistar strain (Rattus norvegicus). Materials and Methods: . This study used a randomized post-test only controlled group design. This in vivo study used two groups of female rats (Rattus norvegicus). Group 1 was treated with the high obese diet for eight weeks, and group 2 was not treated with the high obese diet. After eight weeks, the rats were weighed, the proestrus phase was synchronized, and then the rats were terminated. Results: In this study, there was no significant difference in glycodelin levels between the obese and non-obese groups with a p= 0.821 (p >0.05). Significant differences were found in uterine NK cell expression between obese dan non-obese groups with p=0.001 (p <0.05). The correlation test of glycodelin levels and uterine NK cell expression showed insignificant results with a correlation coefficient of 0.120 and p=0.513. This proved that there was no significant correlation between glycodelin levels and uterine NK cell expression. Conclusion: There was no significant difference between glycodelin levels and uterine NK cell expression in obese and non-obese female white rats of Wistar strain (Rattus norvegicus).